2021
DOI: 10.1002/psp4.12598
|View full text |Cite
|
Sign up to set email alerts
|

Bench‐to‐bedside translation of chimeric antigen receptor (CAR) T cells using a multiscale systems pharmacokinetic‐pharmacodynamic model: A case study with anti‐BCMA CAR‐T

Abstract: Despite tremendous success of chimeric antigen receptor (CAR) T cell therapy in clinical oncology, the dose-exposure-response relationship of CART cells in patients is poorly understood. Moreover, the key drug-and system-specific determinants leading to favourable clinical outcomes are also unknown. Here, we have developed a multiscale mechanistic PK-PD model for anti-BCMA (bb2121) CART cell therapy to characterize 1) in vitro target cell killing in multiple BCMA expressing tumor cell lines at varying E:T rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…Generally, the Holling Type II and III interactions are used to model changes in cell-cell interactions, notably predator-prey handling time and density-dependent behavior. Additionally, where the CARRGO model combines CAR T-cell proliferation and exhaustion into one parameter, κ 2 , other approaches may incorporate a second T-cell type altogether [ 20 , 45 ], a population of macrophages [ 44 ], or explicitly accounting for the pharmacodynamic and pharmacokinetics of CAR T-cell dynamics [ 47 ]. Interestingly, recent theoretical work has shown that a two T-cell type predator-prey model with Holling Type I interactions can, in the appropriate limits and conditions, reduce to a single T-cell type predator-prey model with a Holling Type II interaction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the Holling Type II and III interactions are used to model changes in cell-cell interactions, notably predator-prey handling time and density-dependent behavior. Additionally, where the CARRGO model combines CAR T-cell proliferation and exhaustion into one parameter, κ 2 , other approaches may incorporate a second T-cell type altogether [ 20 , 45 ], a population of macrophages [ 44 ], or explicitly accounting for the pharmacodynamic and pharmacokinetics of CAR T-cell dynamics [ 47 ]. Interestingly, recent theoretical work has shown that a two T-cell type predator-prey model with Holling Type I interactions can, in the appropriate limits and conditions, reduce to a single T-cell type predator-prey model with a Holling Type II interaction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our modeling effort revealed the importance of characterizing CAR T cells fitness over the study duration, for example, using kinetic immunophenotyping, to better understand the cellular kinetics and the duration of response. Emerging efforts in quantitative characterization different phenotypes of CAR T cells have been reported in the literature [ 7 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAR-T cell expansion and persistence are major factors in CAR-T cell treatment, but treatment response is dependent on multiple factors, explaining incongruent results between CAR-T cell kinetics and treatment response. 33 To further understand the kinetics of cfDNA in cellular immunotherapy, simultaneous investigation of CAR-T and lymphoma-derived cfDNA during treatment will be of interest in future studies. 34 Particularly, cfDNA analysis is attractive to investigate both lymphoma-derived DNA and cfCAR-DNA, as it contains DNA fragments from all areas of the body.…”
Section: Discussionmentioning
confidence: 99%